2001
DOI: 10.1056/nejm200107053450101
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Uterine Rupture during Labor among Women with a Prior Cesarean Delivery

Abstract: For women with one prior cesarean delivery, the risk of uterine rupture is higher among those whose labor is induced than among those with repeated cesarean delivery without labor. Labor induced with a prostaglandin confers the highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
381
5
21

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 851 publications
(434 citation statements)
references
References 10 publications
27
381
5
21
Order By: Relevance
“…In the present study, we have no perinatal deaths because we have no uterine ruptures. This is supported by the finding of Lydon-Rochelle et al [8] who found the rate of infant mortality was 5.5% in cases involving uterine rupture, compared with 0.5% without rupture.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the present study, we have no perinatal deaths because we have no uterine ruptures. This is supported by the finding of Lydon-Rochelle et al [8] who found the rate of infant mortality was 5.5% in cases involving uterine rupture, compared with 0.5% without rupture.…”
Section: Discussionsupporting
confidence: 61%
“…It is more likely with shorter interval between pregnancies < 18 months [7], with labor induction or oxytocin augmentation [8], macrocosmic babies [9] and postdates pregnancies [10].…”
Section: Discussionmentioning
confidence: 99%
“…We found a difference in the duration of labor in the two groups, 6 hrs in the group that was induced as against 9.75 hrs in the group that was not induced, a difference of 3.75 hrs (P ≤ 0.001). In a study carried out over four years but with a smaller sample size where misoprostol was matched against oxytocin in induction of twin gestations greater than 34 weeks, the duration of labor in oxytocin group was 15.1 hrs [37].…”
Section: Discussionmentioning
confidence: 99%
“…To decrease the rate of CD, the American College of Obstetricians and Gynecologists recommended that most pregnant women with a single previous low transverse CD be counseled and offered a TOLAC [6]. The risk of uterine rupture in laboring women with a previous CD varies between 0.2% and 1.5% after induction of labor compared with 0.5% in women with spontaneous labor after a previous CD [7] [8]. It is important in the counseling of TOLAC to inform the woman of her chance of success and discuss the maternal and neonatal risks and benefits.…”
Section: Introductionmentioning
confidence: 99%